Transconductance-Mode Gain Controllable First Order Allpass Filter - Piya Supavarasuwat; Montree Kumngern; Winai Jaikla (My University, 2016)
New first order allpass filter (APF) in transconductance mode, constructed from 1 DDCCTA, 1 resistor and grounded capacitor, is presented. The transconductance gain and phase shift can be independently controlled. High input and high output impedances are achieved which make the circuit to be easily cascaded without additional buffers. The magnitude of output current can be electronically adjusted. The operation of the proposed filter has been verified through simulation results using 0.5um MIETEC CMOS technology which confirm the theoretical analysis.
Keywords: All-pass filter; Transconductance; Operational transconductance amplifier; Output impedance; Analog and Mixed-Signal Circuit Design